Relationship between sheep feces scores and gastrointestinal microorganisms and their effects on growth traits and blood indicators - Yang, Xiaobin; Wang, Jianghui; Cheng, Jiangbo; Zhang, Deyin; Huang, Kai; Zhang, Yukun; Li, Xiaolong; Zhao, Yuan; Zhao, Liming; Xu, Dan; Ma, Zongwu; Liu, Jia; et al. (Frontiers in Microbiology, 2024)
Fecal scores are crucial for assessing the digestive and gastrointestinal status of animals. The Bristol fecal scoring system is a commonly used method for the subjective evaluation of host feces, there is limited research on fecal scoring standards for fattening Hu sheep. In this study, we developed scoring criteria with five grades based on the Bristol fecal scoring system, feces morphology, and moisture content in 514 Hu sheep during fattening. It was observed that moisture content significantly increased with higher grades (P < 0.05). We also analyzed the relationship between fecal scores and production traits, blood indices, muscle nutrients, and digestive tract microorganisms. The growth traits (body weight, body height, body length, average daily gain (ADG), and average daily feed intake (ADFI) during 80-180 days), body composition traits of the F3 group, and the carcass traits were found to be significantly higher (P < 0.05) than those of the F1 and F2 groups. There was no significant difference in gastrointestinal microflora diversity among all groups (P > 0.05). Significant differences were observed in Aspartate aminotransferase, Glucose, Total bilirubin, and Red Blood Cell Count between groups (P < 0.05). The mutton moisture content in group F4 was significantly higher than in the other groups, and the protein content was also the lowest (P < 0.05). The results of the correlation analysis demonstrated that Actinobacteria, Peptostreptococcaceae, Acidaminococcales, Gammaproteobacteria, and Proteobacteria were the significant bacteria affecting fecal scores. In addition, Muribaculaceae and Oscillospiraceae were identified as the noteworthy flora affecting growth performance and immunity.